Prolonged lead dwell time and lead burden predict bailout transfemoral lead extraction. Issue 10 (5th September 2019) - Gould, Justin; Sidhu, Baldeep.S.; Porter, Bradley; Sieniewicz, Benjamin. J.; Teall, Thomas; Williams, Steven.E.; Shetty, Anoop; Bosco, Paolo; Blauth, Christopher; Gill, Jaswinder; Rinaldi, Christopher. A.
Abstract: Background: Transvenous lead extraction (TLE) may be performed by superior approach using the original implant vein or via a femoral approach; however, limited comparative data exists. We compare outcomes between femoral versus nonfemoral TLE approaches and determine predictors of bailout transfemoral lead extraction in patients undergoing initial TLE via the original implant vein by a superior approach. Methods: All consecutive TLEs between October 2000 and March 2018 were prospectively collected ( n = 1052). Patients were dichotomized into femoral ( n = 118) and nonfemoral ( n = 934) groups. Results: Demographics were balanced between femoral vs nonfemoral groups. Patients in the femoral group had significantly higher mean lead dwell times (11.6 ± 9.7 vs 6.6 ± 6.6 years, P < .001), mean number of leads extracted (2.7 ± 1.3 vs 2.0 ± 1.0, P < .001), 30‐day procedure related major complications (including deaths) (8.5% vs 1.1%, P < .001) and emergency thoracotomy rates (4.2% vs 0.7%, P = .007). All‐cause 30‐day mortality rates were similar between groups (3.4% vs 2.0%, P = .315). Prolonged lead dwell time and increased number of leads extracted were predictive of a bailout transfemoral approach at multivariable analysis. Conclusion: Femoral approach TLE is associated with increased risk of 30‐day procedure related major complications but not 30‐day all‐cause mortality. Prolonged lead dwell time and increased number of leads extracted are independent predictors for bailout transfemoral lead extraction. Such patients should be considered high risk of major complications and performed by high‐volume lead extraction centers with experience in multiple approaches and techniques including experience with transfemoral lead extraction.